(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Meckel’s diverticulum, the most common congenital anomaly of small bowel although usually silent, can cause complications like intestinal obstruction, bleeding, diverticulitis, perforation etc. We report a case, which presented with acute onset of severe pain in right iliac fossa which was clinically and sonographically diagnosed as acute appendicitis. Histopathological report of appendix was non specific findings. Four days after appendectomy patient again came with features of acute abdomen. X-ray abdomen showed free gas under diaphragm. Abdomen was explored with a midline incision, a perforated Meckel’sdiverticulum was found which was managed by wedge resection and repair of the ileum. Histopathological examination of specimen revealed diverticular wall with normal appearing intestinal mucosa and muscle coat which showed two heterotrophic tissues (pancreatic and gastric ) in the wall.These also showed features of perforation and acute peritonitis. This is probably the first case of Meckel’s diverticulitis with heterotropic pancreatic and gastric tissue in Bangladesh. J Shaheed Suhrawardy Med Coll 2020; 12(2): 115-118